FINANCIAL LITERACY, LIFESTYLE, SELF-CONTROL ON STUDENTS' FINANCIAL BEHAVIOR: FINANCIAL LITERACY, LIFESTYLE, SELF-CONTROL ON STUDENTS' FINANCIAL BEHAVIOR - Sabrina, Bivana C. Sabrina; Milati, Nela Aini Milati; Octavia, Ayu Nurafni (Universitas Wahid Hasyim Semarang, 2024)
This study aims to see financial behavior in active undergraduate students of the Management Faculty of Economics, University of Semarang influenced by financial literacy, lifestyle, and self-control. The population is all active undergraduate management students of the Faculty of Economics, University of Semarang class of 2022, and 96 students as samples selected through the random sampling method. Then, the data used is primary data where the origin is from a questionnaire distributed online. According to the results that have been obtained, it can be concluded: that financial literacy variables have a significant positive effect on financial behavior variables, lifestyle has an insignificant positive effect on financial behavior, self-control has an insignificant negative effect on financial behavior, financial literacy variables, lifestyle, and self-control together affect the financial behavior of active undergraduate students of the Faculty of Economics, University of Semarang class of 2022.